Hadith #2911 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Mu'adh ibn Jabal (Sunan Abi Dawud)
The Prophet (ﷺ) said: people of two different religions would not inherit from one another.
Grade: Hasan Sahih

Hadith #2912 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; Amr bin Abi Hkym عمرو بن أبي حكيم الواسطي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: Islam increases and does not diminish. He, therefore, appointed a Muslim heir (of a non-Muslim).
Grade: Da'if

Hadith #4204 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abdur-Razzaq عبد الرزاق بن همام; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; Abu Dharr al-Ghaffari; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ma'mar bin Rashid معمر بن راشد; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري (Sunan Abi Dawud)
Abu Quhafah was brought on the day of the conquest of Mecca with head and beard while like hyssop. The Messenger of Allah (ﷺ) said: Change this something, but avoid black.
Grade: Sahih

Hadith #4919 - Sunan Abi Dawud - Abd al-Whab bin Aby عبد الوهاب بن أبي بكر; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; al-Rabi' bin Sulaiman bin Da'ud الربيع بن سليمان بن داود; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Nafi' bin Yazid al-Kula'i نافع بن يزيد الكلاعي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
The Prophet (ﷺ) said: Shall I not inform you of something more excellent in degree than fasting, prayer and almsgiving (sadaqah)? The people replied: Yes, Prophet of Allah! He said: It is putting things right between people, spoiling them is the shaver (destructive).
Grade: Sahih

Hadith #5242 - Sunan Abi Dawud - Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; Abu Dharr al-Ghaffari; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان; Yahya bin Aqyl يحيى بن عقيل; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: A human being has three hundred and sixty joints for each of which he must give alms. The people asked him: Who is capable of doing this ? He replied: It may be mucus in the mosque which you bury, and something which you remove from the road; but if you do not find such, two rak’ahs in the forenoon will be sufficient for you.
Grade: Sahih